La percepción del riesgo y su relación con la actual crisis económico-financiera global - Barrera Herrera, Jorge (2009)
The aim of this article is to analyse the main factors of excessive prociclicidad of financial systems, due to increased unnecessary fluctuations in the leve[ of activity which puts at risk the financial stability with a negative impact on the real economy of the countries.The normal real economic growth of a country goes in parallel with the growth of financial systems in general and with the growth of appropriations in particular, causing a logical and desirable prociclicidad very strong among these, always putting in evidence as the balances of payments National correspond as interdependent elements of a global monetary system zero-sum.The problem arises to the extent that there are factors inherent in the behaviour of economic agents acting within the financial systems or arising out of prudential regulation which increase volatility in abnormal form on their levels considered fundamental to have a procyclical impact amplitude in the economic cycle, always inconvenient for the generation of turbulence and volatility in prices.